2000
DOI: 10.1159/000055595
|View full text |Cite
|
Sign up to set email alerts
|

Linoleic Acid Cytotoxicity to Bovine Lens Epithelial Cells: Influence of Albumin on Linoleic Acid Uptake and Cytotoxicity

Abstract: The high cytotoxicity of linoleic acid (LA) to cultured bovine lens epithelial cells is correlated with high uptake rates for the fatty acid (FA). Both, LA uptake and LA cytotoxicity strongly increase with the increasing LA-to-albumin molar ratio in the culture medium. Cellular uptake and cytotoxicity of LA can be competitively inhibited with the noncytotoxic palmitic acid. The findings may be of interest in view of the low albumin concentration in aqueous humor, resulting in extremely low buffering capacities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 13 publications
2
15
0
1
Order By: Relevance
“…Lens cells actively transport albumin from the apical to the basolateral compartment in a process that involves caveolae and clathrin-coated vesicles (167)(168)(169). Micromolar concentrations of unsaturated fatty acids are cytotoxic to cultured bovine and human lens cells (170)(171)(172)(173)(174)(175). The aqueous humor of elderly patients who had cataracts contained micromolar levels of fatty acids and raises the possible involvement of these fatty acids in cataract formation.…”
Section: Systemic Fatty Acids and Cataractmentioning
confidence: 99%
See 1 more Smart Citation
“…Lens cells actively transport albumin from the apical to the basolateral compartment in a process that involves caveolae and clathrin-coated vesicles (167)(168)(169). Micromolar concentrations of unsaturated fatty acids are cytotoxic to cultured bovine and human lens cells (170)(171)(172)(173)(174)(175). The aqueous humor of elderly patients who had cataracts contained micromolar levels of fatty acids and raises the possible involvement of these fatty acids in cataract formation.…”
Section: Systemic Fatty Acids and Cataractmentioning
confidence: 99%
“…In a number of pathophysiologic states related to cataract formation, fatty acid is elevated in blood [see references in ( 175,176 )]. Fatty acid exposure results in bleb formation where fatty acid molecules accumulate in the cells ( 174 ). Bleb formation, disruption of the actin cortical network, and the redistribution of actin are related ( 177,178 ) and contribute to lens opacity.…”
Section: Systemic Fatty Acids and Cataractmentioning
confidence: 99%
“…Though the FA cytotoxicity could be completely eliminated by BSA, it appeared again when the molar FA-to-albumin ratio exceeded 1:1 [2]. Furthermore, it could be shown that both linoleic acid uptake and linoleic acid cytotoxicity strongly increase with increasing linoleic acid-to-albumin molar ratios in the culture medium [3].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to 25 mol/l linoleic or arachidonic acid causes cell retraction, increasing granulation, bleb formation, pycnotic nuclei, and eventually cell detachment ( fi g. 1 b, c), quite similar to what has been described as characteristic morphological signs of fatty acid cytotoxicity with subcultured bovine and human lens epithelial cells [1][2][3][4] . Blebs are the result of lipid accumulation [3] and may appear like brilliant droplets in the cytoplasm ( fi g. 1 c) [4] . One or 5 mol/l linoleic acid, examined up to 96 and 72 h, respectively, were without effects.…”
Section: Resultsmentioning
confidence: 72%